Studying the coherent channel of neutral current ν-nucleus interaction - Tsakstara, V.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2019)
Original cross-sections calculations for neutral current neutrino scattering on 40Ar isotope are performed in the context of the quasi-particle random phase approximation (QRPA) by utilizing realistic two-nucleon forces. The incoming neutrino energy range adopted, εν ≤ 100 MeV, covers the supernova neutrinos, the low-energy beta-beam-neutrinos and the pion-muon stopped neutrino-beams existing or planned to be conducted at future neutron spallation sources. Subsequently, are the original cross sections convoluted with various supernova neutrino-energy distributions such as the two-parameter Fermi-Dirac and the power law distributions. The folded cross sections are obtained for various values of the parameters of these neutrino energy distributions corresponding to different supernova scenarios. One of the main purposes of this work is to explore the response of the 40Ar isotope as supernova neutrino detector.